2009
DOI: 10.1111/j.1447-0349.2008.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with seclusion in a statewide forensic psychiatric service in Australia over a 2‐year period

Abstract: Despite seclusion being described as one of the most ethically- and legally-controversial management options available, it remains a widely-used clinical strategy for managing disruptive, aggressive, and violent behaviour. This study sought to determine how frequently seclusion was used, the common characteristics of those secluded and not secluded, and the degree to which the Level of Service Inventory - Revised: Screening Version (LSI-R: SV) could predict seclusion. The study was retrospective, covering the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 42 publications
(61 reference statements)
4
63
0
Order By: Relevance
“…The rates in forensic units were much lower than those of the two separate HDUs and the general units with a co-located HDU. A twoyear retrospective study of an Australian forensic mental health service found 44% of patients admitted during this period were secluded (Thomas et al, 2009). The relatively low rates in our study could be the result of the inclusion of three rehabilitation wards where patients are often prepared to be transferred to a nonforensic ward or the community.…”
Section: Discussionmentioning
confidence: 68%
“…The rates in forensic units were much lower than those of the two separate HDUs and the general units with a co-located HDU. A twoyear retrospective study of an Australian forensic mental health service found 44% of patients admitted during this period were secluded (Thomas et al, 2009). The relatively low rates in our study could be the result of the inclusion of three rehabilitation wards where patients are often prepared to be transferred to a nonforensic ward or the community.…”
Section: Discussionmentioning
confidence: 68%
“…Although research has examined the attitudes of nurses towards the practice of seclusion (Alty, 1997;Bonner et al, 2002;Duxbury, 2002;Larue et al, 2007;Lee et al, 2003;Lewis, Taylor, & Parks, 2009;Meehan et al, 2004;Moran et al, 2004;Terpstra et al,. 2001; Thomas et al, 2009;Wynaden et al, 2001), interestingly little attention has focused on what factors might underpin or influence these attitudes.…”
mentioning
confidence: 99%
“…Markowitz 2011), leading to changes in the profile of the patient group receiving inpatient care and treatment. With the shift of patient profiles it is perhaps not surprising that violent incidents have increased within public psychiatric hospitals and become a commonplace recurring challenge for staff, especially those at the frontline of psychiatric care provision (Gudjonsson et al 1999, Thomas et al 2009). Indeed, research from the United States of America, United Kingdom, Australia and Canada reports that workplace violence in the healthcare sector has significantly increased over the last decade (RCN 1999, Rippon 2000, Stirling et al 2001, Carter 2002.…”
Section: The Management Of Aggression In Psychiatric Servicesmentioning
confidence: 99%